UPAYA PEMERINTAH ISLANDIA MENANGGULANGI KEKERASAN BERBASIS GENDER 2017-2020 - Qasrhin Bulan Syazdwana; Yessi Olivia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Twelve years in a row, the World Economic Forum has ranked Iceland as the nation with the highest level of gender equality. Even though Iceland has the maximum level of gender equality, there is still gender-based violence. According to Stigamot, an Icelandic survivor center, as many as 12% of Icelandic women reported experiencing gender-based violence, and as many as 40% of women entering college admitted to having experienced such violence. This study employs qualitative methods, with data collected from reputable sources such as books, official publications from the report from Stigamot, journals, and news articles. This study employs the capability theory to argue that violence against women unquestionably affects all economic, educational, social, and environmental factors. A number of efforts have been made by the Icelandic government to combat instances of gender-based violence, including the formation of a steering committee to address gender-based violence in accordance with Goal 5 of the Sustainable Development Goals. The findings of this study indicate that gender-based violence will increase in 2021, despite the fact that it still occurs today. The challenge for the government is the lack of shelters, the reluctance of people to disclose homelessness due to the stigma, and the inefficiency of decisions in Iceland. Keywords: Iceland, Gender Based Violence, Gender Equalit